Application of multi-factorial experimental design to successfully model and optimize inorganic chromium speciation by square wave voltammetry - Cuellar, Mariela (2016)
Response surface methodology (RSM) was used to optimize voltammetric signal of hanging mercury drop electrode (HMDE) for inorganic chromium determination and speciation. Initial solution pH, DTPA (Diethylenetriaminepentaacetic acid) concentration, SWV frequency, pulse height, step potential, accumulation time and accumulation potential were considered as important operating factors through experimental design methodology for Cr(VI) quantification. The central composite and a Box-Behnken designs as response surface design coupled with numerical optimization technique was applied for obtaining the optimum chemical and SWV instrumental conditions as well as the maximum height of chromium reduction peak. Optimum conditions were set as follow: pH 6.5, DTPA concentration 5.5 mmol L- 1, SWV parameters: frequency 500 Hz, step potential 0.005 V, pulse height 0.1 V, accumulation time 120 s and accumulation potential - 1.10 V. Speciation is performed in two separate samples, in the first one Cr(VI) is measured after 40 min and DPTA addition. While in the second one, Ce(IV) is added and all Cr(III) is oxidized to Cr(VI) allowing total chromium determination, finally Cr(III) is obtained by difference. Under the optimal experimental conditions, the current reduction peak was proportional to chromium(VI) concentration in the 5-105 nmol L- 1 range, with detection and quantification limits of 3.77 and 8.47 nmol L- 1, respectively. Using the proposed method, inorganic chromium speciation was successfully determined in water samples with standard addition method, suggesting that this method can be applied to the quantification of inorganic chromium speciation in water samples.